Penyuluhan Dampak Perundungan (Bullying) di Lingkungan Pendidikan pada SMPN 1 Sabbangparu - Firman; Mansur S; Mega Jasa; Ahmad Nur Furqan (Compile Journal of Society Service, 2024)
This community service research aims to increase students' understanding of the impact of bullying in the educational environment. This method was carried out in the form of counselling held at SMPN 1 Sabbangparu, Wajo Regency. The counselling was conducted out of concern for a number of cases of child bullying that often occur in the country. Both bullying by adults against children and bullying between children. Data from the Indonesian Child Protection Commission (KPAI) revealed that there were 3,800 cases of bullying throughout 2023, almost half of which occurred in educational institutions. Meanwhile, the Federation of Indonesian Teachers' Unions (FSGI) noted that in 2022, out of 226 cases of bullying against school children, among them were physical bullying (55.5%), verbal bullying (29.3%), and psychological bullying (15.2%). Based on the level of education, 26% of primary school students were victims of bullying, 25% of junior high school students, and 18.75% of high school students.